The cyborgification of paralympic sport - Howe, P. D.; Silva, C. F. (Movement & Sport Sciences - Science & Motricité, 2017)
Since the turn of the century, the Paralympic movement has gained a high public profile. We will argue that this new high profile is a direct result of the focus of media attention upon new technologies of prosthetic medicine that have helped to create a legion of cyborg bodies that is manifest in the image of the contemporary sporting supercrip. This paper highlights the development of a technocentric ideology that has been embraced within the Paralympic movement. In embracing this ideology, the International Paralympic Committee (IPC) began to celebrate the cyborgification of Paralympic bodies. Ultimately, this paper questions whether the advances in technology are actually empowering all disabled athletes or simply those who have the potential to be cyborgs.